2019
DOI: 10.1055/a-0826-2296
|View full text |Cite
|
Sign up to set email alerts
|

Pneumologische Frührehabilitation nach Langzeitbeatmung

Abstract: Zusammenfassung Einleitung Unter Frührehabilitation versteht man eine frühzeitig bei- oder nach akuter Erkrankung einsetzende, rehabilitationsmedizinische Behandlung die im § 39SGB V verankert ist. Ziel dieser Untersuchung ist es, die Ergebnisqualität der pneumologischen Frührehabilitation zu untersuchen und darzustellen. Methoden Prospektive Erhebung von funktionellen Parametern, Beatmungsstatus und Entlass-Disposition in einer spezialisierten Abteilung für pneumologische Frührehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…According to the study by Dellweg et al [720], a total of 94% of patients had previously received invasive MV, and in 29% of all cases, the ventilation status changed during the early rehabilitation phase. The diagnoses that led to MV were distributed as follows: Infections and sepsis (31.1%), COPD exacerbations (24.2%), elective surgery (22.1%), emergency operations (8.9%), heart diseases (6.3%), neurological diseases (4.2%) and other pulmonary diseases (not COPD, 3.2%).…”
Section: Infrastructure and Process Organisation For The Care Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study by Dellweg et al [720], a total of 94% of patients had previously received invasive MV, and in 29% of all cases, the ventilation status changed during the early rehabilitation phase. The diagnoses that led to MV were distributed as follows: Infections and sepsis (31.1%), COPD exacerbations (24.2%), elective surgery (22.1%), emergency operations (8.9%), heart diseases (6.3%), neurological diseases (4.2%) and other pulmonary diseases (not COPD, 3.2%).…”
Section: Infrastructure and Process Organisation For The Care Of Pmentioning
confidence: 99%
“…From a pneumological perspective, it is important that motor weakness is not just limited to the trunk muscles, but also affects the respiratory muscles to at least the same extent [120]. In this respect, Dellweg et al showed that the outcome after early pneumological rehabilitation in terms of mobility (walking distance) and ADL scores (FAM (Functional Assessment Measure)/Barthel-Index) is comparably good for patients without MV versus those with non-invasive and invasive MV [720]. Another important component from a prognostic and therapeutic point of view is the perception and treatment of dysphagia (see Chapter 5.6.1.5) [722].…”
Section: Infrastructure and Process Organisation For The Care Of Pmentioning
confidence: 99%
“…In der Studie von Dellweg et al [721] waren insgesamt 94 % der Patienten zuvor invasiv beatmet, in 29 % aller Fälle kam es zu einem Wechsel des Beatmungsstatus während der Frührehabilitationsphase. Die zur Beatmung führenden Diagnosen verteilten sich dabei wie folgt: Infektionen und Sepsis (31,1 %), COPD-Exazerbationen (24,2 %), elektiv geplante operative Eingriffe (22,1 %), Notfalloperationen (8,9 %), kardiale Erkrankungen (6,3 %), neurologische Erkrankungen (4,2 %) und anderweitige pulmonale Erkrankungen (nicht COPD, 3,2 %).…”
Section: Patientenkollektivunclassified
“…24 Verteilung der Patienten n= 190 einer pneumologischen Frührehabilitation, aufgeschlüsselt nach Beatmungsstatus und ggf. Beatmungszugang[721]. Rehabilitation ist daher fortwährend zu prüfen, welche weiteren rehabilitativen Verfahren für den jeweiligen Patienten indiziert sind.…”
unclassified
See 1 more Smart Citation